Extent of delivery and utilization of farm advisory services of public and private extension service organizations in Meghalaya - SHARMA, NISHI; GRACE CHIRU, TH D; PADARIA, R N; AHMAD, NAFEES; PUNITHA, P; V, RAMASUBRAMANIAN (The Indian Journal of Agricultural Sciences, 2022)
The study was conducted during 2020–21 in Ri-Bhoi district of Meghalaya with two organizations functioning therein, viz. Krishi Vigyan Kendra (KVK) as public extension organization and Rural Resource Training Centre (RRTC) as private extension organization. The present investigation was aimed to study the extent of delivery of services by these two farm advisory services i.e. KVK and RRTC, over a period of time and extent of utilisation of these by the farmers. The extension programs and activities of the two extension organisations in their adopted villages was documented using descriptive approach. The mean scores of extent of utilisation index of beneficiaries of RRTC were more than that of those of KVK. In KVK, Ri-Bhoi extent of utilization for exhibition is more withmean value of 69.6 and the least utilized farm advisory services was exposure visit with mean value of 1.82 whereas in RRTC, field day was the most utilized farm advisory services with mean value of 67 and New varieties/ inputs (in terms of improved crop seeds, fertilizers, pesticides, weedicides) were the least utilized farm advisory services with mean value of 7.9. The study revealed that both KVK and RRTC were found to be energetically working to cater the needs of farmers, youth and women for providing various kinds of farm advisory services. They appear to be at par as far as the extent of delivery of farm advisory services is concerned.